Mobile-Based Smart Doctor Android Application Design - Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Rodianto Rodianto; M Julkarnain; Dedy Sofian MZ (STMIK Budi Darma, 2021)
Health is a primary need that must be met in people's lives. Health institutions in their services to improve effectiveness and efficiency in their services. With current technological developments, all information can be accessed with various types of devices, namely Android-based smartphones. Android applications, can make it easier for users who can use applications without space and time limits. This information system application can be a solution in data processing and can provide information about health and doctor consultations with patients or patients can search for the doctor's location practice. This application was built using the Java programming language for android with the development method using waterfalls. The results of this study are an Android-based information system application that helps the public in obtaining information, consulting doctors, finding doctors' locations, registering boldly to practice doctors and facilitating data processing